2018
DOI: 10.1080/2162402x.2018.1503032
|View full text |Cite
|
Sign up to set email alerts
|

Trial Watch: Oncolytic viro-immunotherapy of hematologic and solid tumors

Abstract: Oncolytic viruses selectively target and kill cancer cells in an immunogenic fashion, thus supporting the establishment of therapeutically relevant tumor-specific immune responses. In 2015, the US Food and Drug Administration (FDA) approved the oncolytic herpes simplex virus T-VEC for use in advanced melanoma patients. Since then, a plethora of trials has been initiated to assess the safety and efficacy of multiple oncolytic viruses in patients affected with various malignancies. Here, we summarize recent prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 368 publications
(541 reference statements)
0
56
0
Order By: Relevance
“…adoptive T cell therapies, cancer vaccines). [53][54][55][56][57][58][59] Notwithstanding the aforementioned limitations, our results delineate a strategy for tumor treatment that involves a therapy consisting in the administration of three drug classes: (i) ICD inducers exemplified by MTX and OXA, (ii) CRMs exemplified by HC and Spd and substitutable for fasting (if the nutritional status of the patient allows it) and (iii) ICIs targeting the PD-1/PD-L1 interaction. As shown here, such a triple combination has the potential to cure the majority of mice bearing established fibrosarcomas.…”
Section: Discussionmentioning
confidence: 91%
“…adoptive T cell therapies, cancer vaccines). [53][54][55][56][57][58][59] Notwithstanding the aforementioned limitations, our results delineate a strategy for tumor treatment that involves a therapy consisting in the administration of three drug classes: (i) ICD inducers exemplified by MTX and OXA, (ii) CRMs exemplified by HC and Spd and substitutable for fasting (if the nutritional status of the patient allows it) and (iii) ICIs targeting the PD-1/PD-L1 interaction. As shown here, such a triple combination has the potential to cure the majority of mice bearing established fibrosarcomas.…”
Section: Discussionmentioning
confidence: 91%
“…During the treatment and observation period, tumors in the mock group exhibited central necrosis or cavitation when the size increased to 600-1,000 mm 3 . Tumors in the oHSV2 treatment group exhibited necrosis in the early stages of treatment at a size of 100-200 mm 3 , and a local black scab and tumor regression appeared. On day 13 after the first treatment, one mouse in the oHSV2 treatment group exhibited tumor regression.…”
Section: Ohsv2 Treatment Inhibits Tumor Growth and Prolongs Survivalmentioning
confidence: 97%
“…For the past few years, the emergence of virotherapy and in-depth research into it has shed new light on the treatment of solid tumors. 3 Oncolytic viruses (OVs) have attracted much attention because of their unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…By releasing tumor antigens in concert with DAMPs (danger-associated molecular patterns) and PAMPs (pathogen-associated molecular patterns) during viral infection, oncolytic virotherapy acts as an antigen-agnostic in situ tumor vaccine [12]. While the herpes virus talimogene laherparepvec has been approved by the FDA and EMA, several other oncolytic viruses are currently in clinical trials, including vaccinia, adeno-, rhabdo-and reoviruses [13]. Oncolytic measles vaccines are under clinical investigation for treatment of several tumor entities, and early trials have indicated the safety and efficacy of this approach [12].…”
Section: Introductionmentioning
confidence: 99%